A multi-approach monitoring of particulate matter, metals and PAHs in an urban street canyon - De Nicola, Flavia; Murena, Fabio; Costagliola, M. Antonietta; Alfani, Anna; Baldantoni, Daniela; Prati, M. Vittoria; Sessa, Ludovica; Spagnuolo, Valeria; Giordano, Simonetta (ENVIRONMENTAL SCIENCE AND POLLUTION RESEARCH, 2013)
For the first time until now, the results from a prediction model (Atmospheric Dispersion Modelling System (ADMS)-Road) of pollutant dispersion in a street canyon were compared to the results obtained from biomonitors. In particular, the instrumental monitoring of particulate matter (PM10) and the biomonitoring of 14 polycyclic aromatic hydrocarbons (PAHs) and 11 metals by Quercus ilex leaves and Hypnum cupressiforme moss bags, acting as long- and short-term accumulators, respectively, were carried out. For both PAHs and metals, similar bioaccumulation trends were observed, with higher concentrations in biomonitors exposed at the leeward canyon side, affected by primary air vortex. The major pollutant accumulation at the leeward side was also predicted by the ADMS-Road model, on the basis of the prevailing wind direction that determines different exposure of the street canyon sides to pollutants emitted by vehicular traffic. A clear vertical (3, 6 and 9 m) distribution gradient of pollutants was not observed, so that both the model and biomonitoring results suggested that local air turbulences in the street canyon could contribute to uniform pollutant distribution at different heights.
The following values have no corresponding Zotero field: pub-location: TIERGARTENSTRASSE 17, D-69121 HEIDELBERG, GERMANY publisher: SPRINGER HEIDELBERG
Keywords: Holm oak leaves; metals; Moss bags; Naples urban area; PAHs; Pollutant dispersion model

Fireplace and woodstove fine particle emissions from combustion of western Mediterranean wood types - Alves, Célia; Gonçalves, Cátia; Fernandes, Ana Patrícia; Tarelho, Luís; Pio, Casimiro (Atmospheric Research, 2011)
Wood from seven species of trees grown in the Portuguese forest (Pinus pinaster, Eucalyptus globulus, Quercus suber, Acacia longifolia, Quercus faginea, Olea europea and Quercus ilex rotundifolia), and briquettes produced from forest biomass waste were burned in a ﬁreplace and in a woodstove to determine the chemical composition of ﬁne particle (PM2.5) emissions. Samples were analysed for organic and elemental carbon (OC/EC), water soluble ions (Na+ , NH4 + , K+ , Mg 2+ , Ca 2+ , Cl− , NO3 − and SO4 2− ) and 67 elements. The PM2.5 emission factors (g kg−1 fuel burned, dry basis) were in the ranges 9.9–20.2 and 4.2–16.3, respectively, for the ﬁreplace and the woodstove. Organic carbon contributed to about 50% of the ﬁne particle mass in the emissions from every wood species studied in both burning appliances. The carbonaceous component of PM2.5 was dominated by organic carbon, accounting for more than 85% of the total carbon (TC): OC/TC ranged from 0.85 to 0.96 (avg. 0.92) for the ﬁreplace and from 0.86 to 0.97 (avg. 0.93) for the woodstove. The water-soluble ions accounted for 0.64 to 11.3% of the PM2.5 mass emitted from the ﬁreplace, whereas mass fractions between 0.53 and 13.6% were obtained for the woodstove. The golden wattle wood smoke showed a much higher ionic content than the emissions from the other wood types. Trace elements represented 0.4 to 2.5% and 0.2 to 2.2% of the PM2.5 mass emitted, respectively, from the ﬁreplace and the woodstove, which corresponded to average total emissions of 132± 77.3 mg kg−1 and 93.4± 60.8 mg kg−1 of wood burned. Among these, K, Pb, Al, Mn and Sr were present in all samples. From the emission proﬁles of the individual experiments, composite wood combustion proﬁles are suggested with the aid of a cluster analysis.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Biomass burning; Fireplace; metals; OC/EC; PM2.5; Water-soluble ions; Woodstove

Cork and metals: a review - C. C. da Ponte-e-Sousa, João Carlos a; Neto-Vaz, António Manuel; de C. C. da Ponte-e-Sousa, João Carlos a; Neto-Vaz, António Manuel (Wood Science and Technology, 2009)
All published results available regarding ash content and 21 chemical elements were chronologically compiled. The evolution of analytical methodologies, the rising interest in the knowledge of certain elements at a certain time, and the relation between concentrations and time, are among the gathered information within a period of 221 years, starting with the ﬁrst published study from the year 1787. Rather than establish a correlation between the inorganic content of cork and its quality, the aim of this data collection is to remove all doubts regarding what is already known on the inorganic content of cork.
Keywords: ash content; cork (voyant); metals; mineral elements

Cork and metals: a review - C. C. da Ponte-e-Sousa, João Carlos a.; Neto-Vaz, António Manuel; de C. C. da Ponte-e-Sousa, João Carlos a.; Neto-Vaz, António Manuel (Wood Science and Technology, 2009)
All published results available regarding ash content and 21 chemical elements were chronologically compiled. The evolution of analytical methodologies, the rising interest in the knowledge of certain elements at a certain time, and the relation between concentrations and time, are among the gathered information within a period of 221 years, starting with the ﬁrst published study from the year 1787. Rather than establish a correlation between the inorganic content of cork and its quality, the aim of this data collection is to remove all doubts regarding what is already known on the inorganic content of cork.
Keywords: ash content; cork (voyant); metals; mineral elements

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T; Marañón, Teodoro; Murillo, José M; Schulin, Rainer; Robinson, Brett H (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity

Trace element accumulation in woody plants of the Guadiamar Valley, SW Spain: a large-scale phytomanagement case study. - Domínguez, María T.; Marañón, Teodoro; Murillo, José M.; Schulin, Rainer; Robinson, Brett H. (Environmental pollution (Barking, Essex : 1987), 2008)
Phytomanagement employs vegetation and soil amendments to reduce the environmental risk posed by contaminated sites. We investigated the distribution of trace elements in soils and woody plants from a large phytomanaged site, the Guadiamar Valley (SW Spain), 7 years after a mine spill, which contaminated the area in 1998. At spill-affected sites, topsoils (0-25 cm) had elevated concentrations of As (129 mg kg(-1)), Bi (1.64 mg kg(-1)), Cd (1.44 mg kg(-1)), Cu (115 mg kg(-1)), Pb (210 mg kg(-1)), Sb (13.8 mg kg(-1)), Tl (1.17 mg kg(-1)) and Zn (457 mg kg(-1)). Trace element concentrations in the studied species were, on average, within the normal ranges for higher plants. An exception was white poplar (Populus alba), which accumulated Cd and Zn in leaves up to 3 and 410 mg kg(-1) respectively. We discuss the results with regard to the phytomanagement of trace element contaminated sites.
The following values have no corresponding Zotero field: accession-num: 17602809
Keywords: Bioaccumulation; biodegradation; Environmental; Environmental Monitoring; Environmental Monitoring: methods; Heavy; Heavy metal; Heavy: analysis; Mass spectrometry; metals; Mining; Olea; Olea europaea; Olea: chemistry; Phytoremediation; Plant Leaves; Plant Leaves: chemistry; Populus; Populus alba; Populus: chemistry; Quercus; Quercus ilex; Quercus: chemistry; Soil; Soil Pollutants; Soil Pollutants: analysis; Soil: analysis; Spain; Species Specificity